Assessment of residual stress on thin films by laser microtopography - Costa, Manuel F. M. (2011)
Residual stress of as-deposited coatings may cause bending of the coating/substrate system. If residual stresses are present and the overall deflection is small compared with the substrate thickness, then by symmetry the coated substrate will take up a spherical curvature in the region away from the edges. Near the edges a complex stress state will be present. However away from the edges this reverts to a simple stress state where stresses normal to the substrate and shear stresses are zero The three-dimensional inspection of thin films deposited in thin substrates allows the assessment of film’s residual stress. In this communication we report on the use of this method illustrating it by performing the residual stress evaluation PVD onto glass deposited thin films using optical non-destructive and non-invasive microtopographic inspection using an active optical triangulation sensor developed by the first author at the Universidade do Minho. It allows depth measures with resolutions down to 2nm and lateral resolutions down to 1μm. The three dimensional map and corresponding coordinate set obtained allow the calculation of the stress distribution over the film.